2022
DOI: 10.3389/fpls.2022.797294
|View full text |Cite
|
Sign up to set email alerts
|

The Loroxanthin Cycle: A New Type of Xanthophyll Cycle in Green Algae (Chlorophyta)

Abstract: Xanthophyll cycles (XC) have proven to be major contributors to photoacclimation for many organisms. This work describes a light-driven XC operating in the chlorophyte Chlamydomonas reinhardtii and involving the xanthophylls Lutein (L) and Loroxanthin (Lo). Pigments were quantified during a switch from high to low light (LL) and at different time points from cells grown in Day/Night cycle. Trimeric LHCII was purified from cells acclimated to high or LL and their pigment content and spectroscopic properties wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…El Hattab et al [57] reported fucoxanthin in C. spongiosus f. verticillatus. Halocynthiaxanthin acetate and loroxanthin decenoate are more abundant in green algae [58]. Xanthophylls exhibit diverse bioactive properties, such as antioxidant, antitumor, and anti-inflammatory activities [55,56,59].…”
Section: Non-target Screening Of Non-volatile Compounds In Ethanol Ex...mentioning
confidence: 99%
“…El Hattab et al [57] reported fucoxanthin in C. spongiosus f. verticillatus. Halocynthiaxanthin acetate and loroxanthin decenoate are more abundant in green algae [58]. Xanthophylls exhibit diverse bioactive properties, such as antioxidant, antitumor, and anti-inflammatory activities [55,56,59].…”
Section: Non-target Screening Of Non-volatile Compounds In Ethanol Ex...mentioning
confidence: 99%
“…In C. reinhardtii, α-carotene is hydroxylated by the activity of P450 ε/ß-ring hydroxylases (CYP97A and CYP97C) [9] at both C3 positions for the synthesis of lutein, a common, yellow-red colored xanthophyll found in all green plants and their progenitors. The native cellular abundance in C. reinhardtii varies depending on the present light intensity [10], is reported to range between 1.77 and 4.13 mg/g [11][12][13], and was engineered to 8.9 mg/g [12] by the overexpression of Xanthophyllomyces dendrorhous phytoene-β-carotene synthase (crtYB). An alternative strategy, by the overexpression of C. reinhardtii LCYE, resulted in a 2.6-fold increased lutein production (to 0.48 mg/L) [14].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy, by the overexpression of C. reinhardtii LCYE, resulted in a 2.6-fold increased lutein production (to 0.48 mg/L) [14]. Lutein can be further hydroxylated at the C9 position to form loroxanthin by a yet unknown enzyme [15], and the lutein-loroxanthin cycle has a potential function in non-photochemical quenching (NPQ) [10,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%